Entropy Generation Analysis of MHD Micropolar Nanofluid Flow through a Micro Channel - Madhu, Macha; Shashikumar, N.S.; Gireesha, B.J.; Kishan, Naikoti (Discontinuity, Nonlinearity, and Complexity, 2026)
Present study analyzes the phenomena of entropy generation of magneto micropolar nanofluid through microchannel with constant pressure gradient. The energy efficiency has been analyzed via entropy generation of the system. The dimensionless two-point boundary value problem acquired from governing equations via dimensionless variables. The nonlinear system is tackled by using Runge-Kutta-Fehlberg scheme. An appropriate comparison has been made with previously published results in the literature as a limiting case of the considered problem. The comparison confirmed an excellent agreement. Influences of flow controlling parameters on velocity, microrotation, temperature, entropy generation number and Bejan number profiles are exemplified quantitatively through graphs. From the comprehensive parametric study, it is established that the entropy production can be improved with Joule heating, convective heating and viscous dissipation aspects.